ANATOMICAL VARIATIONS OF EXTRAHEPATIC BILIARY SYSTEM (Iraqi Journal of Medical Sciences, 2016)
Background:Variations in the anatomy of gallbladder, bile ducts and the arteries that supply them are important to the surgeon during cholecystectomy, because failure to recognize them may lead to inadvertent iatrogenic injuries.Objective:To evaluate the type and frequency of anatomical variations of extra hepatic biliary system encountered during cholecystectomy.Methods: One hundred and fifty patients with gallstones underwent cholecystectomy at Baghdad Teaching Hospital. There comprised 112 females and 38 males with age range between 20-80 years. Open (33 cases) and laparoscopic (117 cases) cholecystectomies were done. Extra hepatic biliary tree was carefully dissected to study the variations in the anatomy of the gallbladder, bile ducts, and the arteries that supply them.Results:There were only three important vascular and four important ductal anomalies while gallbladder anomalies were rare. The total numbers of the extrahepatic biliary anomalies were 81 cases (incidence 54%), and included vascular anomalies (60 cases = 40%); ductal anomalies (18 cases = 12%); gallbladder anomalies (3 cases = 2%); mostly occurred as Phrygian cap (2 cases = 1.3%). The higher incidence of anatomical abnormalities was found in females 80% (65 cases) while in males 20% (16 cases).Conclusion:Anomalies of the vascular and ductal components of the extra hepatic biliary tree are relatively common (the former occurring much more frequently than the latter). Failure to recognize them during biliary surgery leads to iatrogenic injuries and can increase morbidity and mortality.Key Words:Extra hepatic biliary tract; biliary anomalies, cholecystectomy.
Keywords: Extra hepatic biliary tract biliary anomalies; cholecystectomy